Islands in trade: Disentangling distance from border effects - José Luis Groizard; Helena Marques; María Santana (Economics: The Open-Access, Open-Assessment E-Journal, 2014)
Trade between regions separated by a sea border is affected by specific transport costs that have not been considered by the border effects literature. Among these are the existence of a time barrier, the need to combine different transport modes, or to pay fees and taxes for the use of public infrastructures such as ports and airports. The empirical strategy used to estimate the 'island effect' proceeds in two steps: first an augmented gravity model is estimated for mainland and island regions; then a Blinder-Oaxaca decomposition is applied to the gravity estimation results in order to disentangle the distance and border effects for those regions. Results show that island regions are at a substantial disadvantage compared to continental regions, which is due to the higher and non-linear effect of distance coefficients.
Keywords: F15; C23; 330; Gravity equation; border effects; panel data; Spain; regional trade